Advantages and disadvantages of restorative justice in child victimization - Jullien de Asís, Jessica (UNIVERSITAS. Revista de Filosofía, Derecho y Política, 2022)
Even with the rise of Restorative Justice and the variety of existing tools, there are few references to the participation of minor victims in these practices, except for those cases processed by the Juvenile Justice system. There are no prohibitions in this sense, except in cases of gender violence, which invites to reflect on possible advantages and obstacles in the participation of underage victims in these practices.